(untitled) (Cardiovascular Journal, 2022)
Background: In anterior ST-segment elevation myocardial infarction (STEMI), attention paid mainly to the left ventricle. The predictive significance of right ventricular (RV) dysfunction in patients with anterior STEMI has been frequently neglected. In this study, we evaluated the prognostic effect of RV dysfunction on in-hospital outcomes in patients with first anterior STEMI. Methods: Present study is based on the analysis of 77 patients admitted to Coronary care unit of the Sir Salimullah Medical College & Mitford Hospital, Dhaka during April, 2019 to March, 2020, with acute anterior wall myocardial infarction. 12 lead ECG with thorough physical examination was done along with echocardiographic assessment of RV and LV function within index hospitalization, preferably within 24 hours of admission. Patients were divided into two groups depending on right ventricular function assessment. Group I included anterior MI with right ventricular dysfunction and group II included anterior MI without right ventricular dysfunction. In hospital outcomes were observed and compared between two groups. Results: Patients with RV dysfunction had statistically significant higher incidence of cardiogenic shock (22.2 % vs. 2.4%, p < 0.05), acute heart failure (69.4% vs. 24.4%, p < 0.05), arrhythmia (11.1% vs. 0.0%, p < 0.05), increase length of hospital stay in patients of RV dysfunction group. In-hospital mortality was non significantly higher in RV dysfunction group (8.3% vs. 2.4%, p > 0.305). Conclusion: In this study, we observed that in-hospital outcomes were worse in patients with anterior STEMI with RV dysfunction and demands more intense invasive management. Thus, special care should be given for the assessment function of right ventricle in anterior STEMI. Cardiovasc j 2022; 14(2): 128-134